Thermally conductive interface layer containing nanosilver material

CN122941371APending Publication Date: 2026-10-20XIYUE TECHNOLOGY (CHENGDU) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611300283.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-26
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

现阶段主流高性能计算芯片的热流密度已突破100W/cm²,芯片单位面积产热大幅增加,对散热系统的导热效率、稳定性及适配性提出了更高要求,传统散热技术已无法适配高功率芯片的散热需求

Benefits of technology

(1)本发明的导热界面层可以在待冷却器件的工作温度范围内发生相变进入粘弹态,使得导热能力大幅升高,导热能力的升高又阻止或抑制了温度的进一步升高,从而将导热界面层维持在高导热的相变状态中;而且,由于导热界面在工作状态下能够发生相变而软化,因此该导热界面层无需制作成厚度均匀的薄片,而是可以在使用期间自动软化达到自动平整且消除与冷板或待冷却器件之间的空隙,从而在保证散热能力的情况下大幅降低制备难度和成本。简言之,本发明的导热界面层在固态时平整易贴合安装,受热软化后流动性大幅提升,能填满芯片、散热器之间微米级凹凸间隙,大幅减小空气热阻(空气导热极差)。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention relates to a thermally conductive interface layer containing nano-silver material, characterized by comprising: a thermally conductive material configured to conduct heat between a heat sink and a heating element, the thermally conductive material comprising diamond micropowder and nano-silver particles; and a phase change material configured to undergo a reversible phase transition within the operating temperature range of the heating element to enter a viscoelastic state, wherein the phase change material in the viscoelastic state promotes an increase in the thermal conductivity of the thermally conductive material, thereby maintaining the phase change material within a temperature range defined by a lower limit temperature and an upper limit temperature; the phase change material and the thermally conductive material are mixed together. The thermally conductive interface layer of this invention has excellent thermal conductivity, meeting the high-efficiency heat dissipation requirements of high-power semiconductor devices; it will not cause short-circuit faults in semiconductor devices during application, exhibits high safety and stability, and will not corrode metal cold plates.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of thermally conductive interface materials, and more particularly to a thermally conductive interface layer containing nano-silver materials. Background Technology

[0002] With the continuous iteration and upgrading of semiconductor manufacturing process nodes, the integration and computing performance of chips have been greatly improved, and the power density of devices has increased dramatically. At present, the heat flux density of mainstream high-performance computing chips has exceeded 100W / cm², and the heat generation per unit area of ​​the chip has increased significantly. This places higher demands on the thermal conductivity, stability and adaptability of the heat dissipation system, and traditional heat dissipation technologies can no longer meet the heat dissipation needs of high-power chips.

[0003] Traditional thermal interface materials have insufficient thermal conductivity, making it difficult to meet the heat dissipation requirements of high-power devices. Currently, the most widely used thermal interface materials in industrial applications, such as thermal grease and thermal pads, cannot quickly dissipate the large amount of heat generated by high-power chips during operation. This can easily lead to heat buildup on the chip, causing the chip temperature to exceed the optimal operating temperature range, thus failing to meet the high-efficiency heat dissipation requirements of next-generation high-power semiconductor devices.

[0004] To improve thermal conductivity, existing high-end heat dissipation solutions attempt to use gallium-based liquid metal as a thermal interface material. Although this material has excellent thermal conductivity, it is also electrically conductive, which can easily cause short circuits in chip circuits during application. At the same time, gallium-based liquid metal is highly corrosive to aluminum heat sinks, which will accelerate the aging and damage of the heat dissipation structure. Moreover, the material is extremely difficult to clean up after leakage, which seriously affects the reliability and lifespan of chip devices and cannot be adapted to mass production and long-term commercial scenarios.

[0005] In summary, there is an urgent need for a thermal interface material that combines ultra-high thermal conductivity with high safety and stability. Summary of the Invention

[0006] To address at least some of the problems mentioned above in the prior art, the present invention provides a thermally conductive interface layer containing nano-silver material, comprising: A thermally conductive material configured to conduct heat between a heat sink and a heat-generating element, said thermally conductive material comprising diamond micropowder, silver nanoparticles, and optionally one or more of alumina, boron nitride, silicon carbide, zinc oxide, and aluminum powder; and A phase change material is configured to undergo a reversible phase change to enter a viscoelastic state within the operating temperature range of a heating element, wherein the phase change material in the viscoelastic state promotes an increase in the thermal conductivity of a thermally conductive material, such that the phase change material is maintained within a temperature range consisting of a lower limit temperature and an upper limit temperature; the phase change material and the thermally conductive material are mixed together.

[0007] Furthermore, the lower limit temperature is between 15°C and 25°C, and the upper limit temperature is between 50°C and 70°C.

[0008] Furthermore, the phase change material is a silicon-based binder, formed by an addition reaction of hydrogen-containing silicone oil and α-olefin-modified siloxane: Hydrogen-containing silicone oil with the structure shown in Formula I: (Formula I), where 10≤a≤100, 2≤b≤50, 2≤c≤30, R1, R2, R3, R4, R7 are methyl, ethyl or C4~C8 straight-chain or branched alkyl, R6 is methyl, and R5 is C6~12 straight-chain or branched alkyl. α-olefin modified siloxanes with the structure shown in Formula II: (Formula II), R9, R10, R11, R13, and R14 are methyl, ethyl, or C6-C12 straight-chain or branched alkyl groups, R8 and R15 are alkenyl groups, R14 is methyl or C18-C30 straight-chain or branched alkyl groups, and 20 ≤ d ≤ 30.

[0009] Furthermore, R1, R2, R3, R4, R6, and R7 are methyl groups, and R5 is a C8 straight-chain or branched alkyl group; and / or R9, R10, R11, R13, and R14 are methyl, R8 is vinyl, R15 is vinyl, and R12 is a straight-chain or branched alkyl group of C24-C26 or C31-C39; and / or The molar ratio of hydrogen atoms in the Si-H of hydrogen-containing silicone oil to carbon-carbon double bonds in α-olefin-modified siloxanes is 0.5 to 1.2.

[0010] Furthermore, the mass percentage of thermally conductive material in the thermal interface layer is greater than or equal to 90%; and / or The mass percentage of phase change material in the thermally conductive interface layer is 5%-8%.

[0011] Furthermore, the mass percentage of the silver nanoparticles in the thermally conductive interface layer is 0.2%-3%; The nano-silver particles have a particle size of 1 nm-100 nm and are dispersed in the phase change material to form additional thermal conductivity pathways.

[0012] Furthermore, the particle size of the silver nanoparticles is 5 nm-50 nm.

[0013] Furthermore, the thermally conductive material also includes one or more of the following: alumina, boron nitride, silicon carbide, zinc oxide, and aluminum powder.

[0014] Furthermore, the thermally conductive material includes diamond micron powder, zinc oxide, aluminum powder, and nano-silver particles.

[0015] Furthermore, the phase change material can chemically react with the metal surface of the cold plate at the heating temperature and bond with the metal surface.

[0016] The present invention has at least the following beneficial effects: (1) The thermally conductive interface layer of the present invention can undergo a phase transition into a viscoelastic state within the operating temperature range of the device to be cooled, thereby significantly increasing its thermal conductivity. This increased thermal conductivity, in turn, prevents or inhibits further temperature increases, thus maintaining the thermally conductive interface layer in a high thermal conductivity phase transition state. Moreover, since the thermally conductive interface can undergo a phase transition and soften under operating conditions, the thermally conductive interface layer does not need to be made into a thin sheet with uniform thickness. Instead, it can automatically soften during use to achieve automatic flatness and eliminate gaps between the interface layer and the cold plate or the device to be cooled, thereby significantly reducing the manufacturing difficulty and cost while ensuring heat dissipation capacity. In short, the thermally conductive interface layer of the present invention is flat and easy to install in its solid state. After softening under heat, its fluidity is greatly improved, which can fill the micron-level uneven gaps between the chip and the heat sink, significantly reducing air thermal resistance (air has extremely poor thermal conductivity).

[0017] (2) The thermal interface layer of the present invention can react chemically with the metal surface to form a whole with the thermal interface layer and the cold plate, eliminating the thermal interface between the two and improving the thermal conductivity; moreover, by providing the composite of the thermal interface layer and the cold plate as a finished product, the user is exempt from the need to install the thermal interface layer on the cold plate, but can directly install it on the device to be cooled for use.

[0018] (3) The thermal interface layer of the present invention has a high thermal conductivity and strong thermal conductivity, which enables high-power devices to operate within a suitable temperature range and meet the high-efficiency heat dissipation requirements of high-power devices.

[0019] (4) The thermal interface layer of the present invention is insulated, and will not cause short circuit faults in semiconductor devices during application. It has high safety and stability and will not corrode metal cold plates.

[0020] (5) The thermal interface layer of the present invention is easy to use. After use, it can be manually peeled off when cooled to room temperature. The thermal interface layer can be removed without disassembly tools, which greatly simplifies the chip maintenance, replacement and reinstallation process.

[0021] (6) The main materials of the thermal interface layer of the present invention include hydrogen-containing silicone oil, α-olefin modified siloxane, diamond micro powder, etc., which have low cost.

[0022] (7) Furthermore, the thermally conductive interface layer (diamond filler + silicon-based binder) of the present invention is different from commonly used phase change thermal conductive materials (e.g., paraffin wax + alumina / aluminum nitride filler). These phase change thermal conductive materials melt or liquefy during phase change, resulting in loss or failure of the phase change material. Moreover, the filling ratio remains basically unchanged after melting, and its own λ (thermal conductivity) remains basically constant. There is no instantaneous increase in thermal conductivity after melting. The thermally conductive interface layer of the present invention does not melt or liquefy during phase change, but enters a softened viscoelastic state. After entering the viscoelastic state, the diamond tends to assemble into a closely packed phase to reduce the free volume, reduce the internal thermal resistance, and significantly increase the thermal conductivity. The definition of the viscoelastic state is as follows: The intermediate mechanical state of polymer materials between the glassy state and the elastic state, or the transition from the elastic state to the fluid dynamic state, possessing both elastic (solid rebound) and viscous (fluid creep, irreversible flow) properties, is called the viscoelastic state. Attached Figure Description

[0023] To further illustrate the above and other advantages and features of the various embodiments of the present invention, a more specific description of the embodiments of the invention will be presented with reference to the accompanying drawings. It is to be understood that these drawings depict only typical embodiments of the invention and are therefore not intended to limit its scope. In the drawings, identical or corresponding parts will be indicated by identical or similar reference numerals for clarity.

[0024] Figure 1 A cross-sectional structural schematic diagram of a thermally conductive interface layer and a heat sink assembly according to the present invention is shown.

[0025] Figure 2 A cross-sectional structural diagram of a thermally conductive interface layer according to the present invention is shown.

[0026] Figure 3 A schematic diagram of the structure of the thermally conductive interface layer of the present invention in application is shown.

[0027] Figure 4 A schematic diagram showing the contact between the bottom layer diamond and the cold plate after the thermally conductive interface layer of the present invention is shown. Detailed Implementation

[0028] It should be noted that the components in the accompanying drawings may be shown exaggerated for illustrative purposes and may not be to scale.

[0029] In this invention, the various embodiments are merely intended to illustrate the solutions of the invention and should not be construed as limiting.

[0030] In this invention, unless otherwise specified, the quantifiers “a” and “one” do not exclude scenarios involving multiple elements.

[0031] It should also be noted that within the scope of this invention, the terms "same", "equal", and "equal to" do not mean that the two values ​​are absolutely equal, but allow for a certain reasonable error. In other words, the terms also cover "substantially the same", "substantially equal", and "substantially equal to".

[0032] It should also be noted that in the description of this invention, the terms "center," "longitudinal," "lateral," "upper," "lower," "front," "rear," "left," "right," "vertical," "horizontal," "top," "bottom," "inner," and "outer," etc., indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. They are used only for the convenience of describing the invention and for simplifying the description, and do not explicitly or implicitly suggest that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on the invention. Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance.

[0033] Furthermore, the embodiments of the present invention describe the process steps in a specific order. However, this is only for the convenience of distinguishing each step, and is not a limitation on the order of each step. In different embodiments of the present invention, the order of each step can be adjusted according to the process.

[0034] Figure 1 A cross-sectional structural schematic diagram of a thermally conductive interface layer and a heat sink assembly according to the present invention is shown.

[0035] like Figure 1 As shown, the thermal interface layer 200 is attached to the surface of the heat sink 100. The heat sink 100 is a metal cold plate.

[0036] Figure 2 A cross-sectional structural diagram of a thermally conductive interface layer according to the present invention is shown. Figure 3 A schematic diagram of the structure of the thermally conductive interface layer of the present invention in application is shown.

[0037] like Figure 2 and 3 As shown, a thermally conductive interface layer 200 disposed between a heat sink and a heat-generating element includes: Thermally conductive material 201, configured to conduct heat between heat sink 100 and heat-generating element 300, includes diamond micron powder and optionally one or more of alumina, boron nitride, and silicon carbide; and Phase change material 202 is configured to undergo a reversible phase change to enter a viscoelastic state within the operating temperature range of heating element 300. In this viscoelastic state, the phase change material promotes increased thermal conductivity of the thermally conductive material, thereby maintaining the phase change material within a temperature range defined by a lower limit temperature (15°C to 25°C) and an upper limit temperature (50°C to 70°C). Phase change material 202 and thermally conductive material 201 are mixed together. The phase change material does not liquefy within the stated temperature range, maintaining its viscoelastic state without flowing.

[0038] The phase change material 202 accounts for 5%-8% of the thermally conductive interface layer 200. The phase change material is a silicon-based binder, formed by an addition reaction between hydrogen-containing silicone oil and α-olefin-modified siloxane.

[0039] Hydrogen-containing silicone oil has the structure shown in Formula I: (Formula I), where 10≤a≤100, 2≤b≤50, 2≤c≤30, R1, R2, R3, R4, and R7 can be methyl, ethyl, or C4~C8 straight-chain or branched alkyl groups, R6 can be methyl, and R5 can be a C6~C12 straight-chain group.

[0040] α-olefin-modified siloxanes have the structure shown in Formula II: (Formula II) R9, R10, R11, R13, and R14 can be methyl, ethyl, or C6-C12 straight-chain or branched alkyl groups, R8 and R15 are alkenyl groups, and R14 is methyl or C18-C30 straight-chain group, with 20 ≤ d ≤ 30.

[0041] The side chains of hydrogen-containing silicone oil contain Si-H bonds, and the two ends of α-olefin-modified siloxanes contain carbon-carbon double bonds, serving as crosslink acceptors for hydrosilylation reactions. Hydrogen-containing silicone oil and α-olefin-modified siloxanes can undergo an addition reaction catalyzed by a platinum-based catalyst to generate phase change materials. The molar ratio of hydrogen atoms in the Si-H chains of the hydrogen-containing silicone oil to the carbon-carbon double bonds in the α-olefin-modified siloxane is 0.5 to 1.2, for example, 0.8, 0.9, 1.0, 1.1, or 1.2, preferably 0.8 to 1.0.

[0042] In phase change materials, carbon chains with more than 18 carbon atoms directly bonded to silicon atoms undergo crystallization or decrystallization at the softening point (e.g., room temperature 25°C). When the temperature is above the softening point, the phase change material undergoes decrystallization and a phase transition to enter the viscoelastic state. When the temperature drops below the softening point, the phase change material undergoes crystallization and hardens into a solid state.

[0043] In hydrogen-containing silicone oil, the R5 group acts as a solvent for the long carbon chains (more than 18 carbon atoms) in α-olefin-modified siloxanes. The higher the R5 content, the more pronounced the solvent effect, and the lower the phase transition temperature. Therefore, by adjusting the ratio of a and b in the chemical formula (Formula I) of the hydrogen-containing silicone oil, the phase transition temperature of the phase change material can be precisely controlled: adjusting the ratio of a and b within the range of a and b values ​​can change the relative proportion of R5. When the relative proportion of R5 is larger, the phase transition temperature is relatively lower; when the relative proportion of R5 is smaller, the phase transition temperature is relatively higher. The value of a is between 10 and 100, and the value of b is between 2 and 50. When these values ​​are exceeded, the silicone-based binder does not exhibit a phase transition phenomenon.

[0044] The main difference between the phase change material (silicone binder) of the present invention and paraffin wax is that paraffin wax is in a liquid state after phase change, while the phase change material of the present invention is in a viscoelastic state after phase change. The two are fundamentally different.

[0045] Phase change materials (PCMs) also serve to bond diamond particles to metal surfaces and impart mechanical strength to the material. When heated, PCMs can chemically react with and bond to the metal surface of a cold plate. Specifically, PCMs contain Si-H bonds, and the metal surface includes hydroxyl groups (-OH). The Si-H bonds in the PCM react with the hydroxyl groups on the metal surface to form chemical bonds.

[0046] The main component of the thermally conductive material in the thermally conductive interface layer is diamond micropowder, and its content is greater than the sum of the contents of other thermally conductive materials in the interface layer. The particle size of the diamond micropowder is 10μm-100μm. When the thermally conductive material contains only diamond micropowder or diamond micropowder and nano-silver, the proportion of diamond micropowder can reach over 90%. The diamond particles in the thermally conductive interface layer have extremely high thermal conductivity (2000W / (m·K)), serving as the main framework of the thermal conduction pathway. The high filling ratio ensures the formation of a continuous heat conduction network, resulting in a high basic thermal conductivity of the thermally conductive interface layer, which can even reach over 12W / (m·K). The diamond particles are polyhedral in shape.

[0047] When the phase change material in the thermal interface layer undergoes a phase transition to a viscoelastic state upon heating, the volume of the thermal interface layer increases and its hardness decreases. This causes the diamond to tend to assemble into a closely packed configuration, thereby reducing free volume, lowering thermal resistance, and improving the thermal conductivity of the thermal interface layer.

[0048] Moreover, such as Figure 4As shown, after the phase change material undergoes a phase change, a portion of the diamond adjacent to the cold plate naturally settles onto the metal surface of the cold plate. Furthermore, since the diamond is polyhedral, it forms surface contact with the metal surface, significantly increasing the heat conduction area. Because the material enters a viscoelastic state rather than a liquid state after the phase change, the diamond does not move significantly due to gravity. The amount of diamond in the upper half of the vertical path does not decrease due to settling, thus not affecting the vertical heat conduction path.

[0049] During use, a portion of the bottom layer of diamond embeds into the surface of the cold plate metal, further increasing the heat-conducting surface area. When aluminum powder is also included in the heat-conducting material in addition to diamond, an electronic heat transfer path is created between the aluminum atoms, which can further reduce the contact thermal resistance of the heat-conducting interface layer.

[0050] Platinum-based catalysts can be, for example, chloroplatinic acid catalysts, platinum catalysts, etc.

[0051] The aforementioned thermally conductive interface layer may also selectively include silver nanoparticles with a particle size of 1 nm to 100 nm, preferably 5 nm to 50 nm, which are dispersed in the phase change material to form additional thermally conductive pathways, further improving the thermal conductivity of the thermally conductive interface layer. The proportion of silver nanoparticles in the thermally conductive interface layer is 1% to 3%.

[0052] After the phase change material undergoes a phase change (viscoelastic state), the silver nanoparticles form a thermally conductive pathway in the micro-gap of the phase change material, which greatly reduces the contact thermal resistance of the thermally conductive interface layer.

[0053] Within the thermally conductive interface layer, electronic thermal conduction pathways are formed between silver particles or between silver particles and aluminum (optional). Electronic thermal conduction pathways can also be formed between the silver particles and the cold plate metal. These electronic thermal conduction pathways have lower thermal resistance than phonon thermal conduction pathways, thus significantly reducing the contact thermal resistance of the thermally conductive interface layer. The method for manufacturing the thermally conductive interface layer is described below.

[0054] Step 1, preparing the thermally conductive material, includes: mixing diamond micro powder and one or more of the optional alumina, boron nitride, and silicon carbide according to the target filling ratio.

[0055] Step 2, preparing phase change material, includes: mixing hydrogen-containing silicone oil and α-olefin modified siloxane in a certain proportion, adding platinum-based catalyst, and stirring evenly under low temperature (50°C to 80°C) and light-protected conditions.

[0056] Step 3: Mix the thermally conductive material and the phase change material evenly to obtain a thermally conductive slurry.

[0057] Step 4: Perform plasma treatment on the surface of the metal cold plate to introduce hydroxyl groups.

[0058] In one embodiment, hydroxyl groups are introduced onto the surface of the metal cold plate by plasma cleaning or corona treatment (corona discharge).

[0059] Metal cold plates, such as aluminum cold plates, naturally have an oxide layer on their surface. Under normal temperature and natural conditions, aluminum oxide can slowly hydrate to generate hydroxyl groups, but the number of hydroxyl groups is small and easily masked by contaminants. Oxygen-containing plasma cleaning removes surface contaminants on the one hand, and generates a large number of oxygen dangling bond active sites on the aluminum oxide surface on the other hand. The interaction of these active sites with water vapor significantly increases the hydroxyl density on the aluminum surface.

[0060] The aluminum cold plate is surface activated by air corona discharge; the high-energy particles generated by the corona discharge remove organic pollutants from the surface of the cold plate and generate unsaturated active sites on the aluminum oxide layer; the active sites combine with the ambient water vapor to form high-density hydroxyl groups on the metal surface.

[0061] Step 5: Apply thermally conductive paste to the surface of the plasma-treated metal cold plate with a coating thickness of 150μm to 350μm, preferably 200-250μm.

[0062] Step 6: Heat the metal cold plate to 60°C~120°C to solidify the thermally conductive paste and form a thermally conductive interface layer, wherein the thermally conductive interface layer is bonded to the metal cold plate through chemical bonds.

[0063] The preferred metal cold plate is an aluminum cold plate, and the thermally conductive interface layer is bonded to the aluminum cold plate through Si-O-Al chemical bonds.

[0064] In use, the thermally conductive interface layer is located between the heat sink (e.g., a metal cold plate) and the heating element. The heating element generates heat, which heats the thermally conductive interface layer. When the temperature reaches the phase change temperature range of the phase change material, the phase change material changes from a solid state to a viscoelastic state. Simultaneously, the heat sink absorbs the heat transferred by the thermally conductive material in the thermally conductive interface layer. The phase change material is maintained within the temperature range defined by the lower and upper limits of the temperature range, and remains in a viscoelastic state. The phase change temperature range is 25°C to 60°C (preferably 35°C to 50°C or 25°C to 45°C), and the operating temperature range is 25°C to 155°C.

[0065] After use, once cooled to 10°C below the softening temperature, the thermal interface layer can be peeled off without tools, greatly simplifying the chip maintenance, replacement, and reinstallation process.

[0066] The present invention also provides a composite cold plate, comprising a cold plate and the above-mentioned thermally conductive interface layer, wherein the thermally conductive interface layer and the metal surface are bonded together by Si-O-metal chemical bonds.

[0067] The embodiments of the present invention will be described in detail below. These embodiments are implemented based on the technical solution of the present invention, and detailed implementation methods and specific operation processes are given. However, the scope of protection of the present invention is not limited to the following embodiments.

[0068] The components used in the examples and comparative examples are described below.

[0069] Components used in the examples: Hydrogen-containing silicone oil: a mixture based on general formula A-1: (A-1), a: 10~20, b: 0~20; c: 5~10.

[0070] α-Olefin-modified siloxanes: mixtures based on general formulas B-1 and B-2: (B-1), R9, R10, R11, R13, and R14 are methyl, R8 is vinyl, R15 is vinyl, R12 is a C24-C26 straight-chain or branched alkyl group, and d = 20~40.

[0071] (B-2), R9, R10, R11, R13, and R14 are methyl, R8 is vinyl, R15 is vinyl, and R12 is a straight-chain or branched alkyl group with 30 or more carbon atoms, such as a straight-chain or branched alkyl group with C31 to C39, and d = 20 to 40.

[0072] Diamond micron powder C-1 has a particle size of 20μm-50μm.

[0073] Diamond micron powder C-2 has a particle size of 50μm-80μm.

[0074] Chloroplatinic acid catalyst.

[0075] Nano-silver particles with a particle size of 5nm-50nm.

[0076] Zinc oxide particles with a particle size of 0.2μm-0.4μm.

[0077] Aluminum powder with a particle size of 1μm~10μm.

[0078] The following is a description of the components used in the examples, expressed as a percentage by mass, as shown in Table 1.

[0079] Hydrogen-containing silicone oil (A-1) and α-olefin-modified siloxane (B-1 or B-2) were mixed according to a specified ratio, and a chloroplatinic acid catalyst was added. The mixture was stirred evenly under light-protected conditions at 50°C-80°C to form a phase change material. The thermally conductive material and the phase change material listed in the table were mixed evenly according to a specified ratio to obtain a thermally conductive slurry. The surface of the aluminum cold plate was subjected to plasma treatment to introduce hydroxyl groups. The thermally conductive slurry was coated onto the plasma-treated surface of the aluminum cold plate to a thickness of 200 μm. The aluminum cold plate was heated to 60°C-120°C to allow the thermally conductive slurry to form a thermally conductive interface layer.

[0080] Comparative Example 1 Silicone grease thermal conductive materials consist of components in the following table with the indicated mass percentages.

[0081] Comparative Example 2 The high-temperature phase change thermal conductive material comprises the components shown in the table below by mass percentage.

[0082] Comparative Example 3 The high-temperature phase change thermal conductive material comprises the components shown in the table below by mass percentage.

[0083] Comparative Example 4 The thermally conductive gel comprises the components in the mass percentages shown in the table below.

[0084] The following describes the methods for thermal conductivity testing, phase transition testing, electrical conductivity testing (breakdown voltage), and stability verification.

[0085] Thermal conductivity was tested according to ISO 22007.

[0086] The thermal conductivity test method includes: placing the thermally conductive interface layer of Examples 1-5 and the thermally conductive material of Comparative Examples 1-4 between the chip and the cold plate, respectively, testing the chip temperature under 100% load for 1000 hours, and recording the highest temperature of the chip as the thermal conductivity test data.

[0087] Differential thermal analysis (DTA) was used to test the phase transition temperature of the material using a differential thermal analyzer.

[0088] Thermogravimetric analysis (TGA) was used to test the stability of the thermally conductive interface layers of Examples 1-5 and the thermally conductive materials of Comparative Examples 1-4, and to examine their thermal weight loss at 200 degrees Celsius.

[0089] The breakdown voltage of the material is tested according to GBT1408.

[0090] The following are the test results for the examples and comparative examples.

[0091] When the thermal weight loss exceeds 1%, it is considered unqualified. The thermally conductive interface layer of Example 3 does not contain hydrogen-containing silicone oil, and its thermal weight loss is as high as 4%, far exceeding that of Examples 1, 2, 4, and 5, and its breakdown voltage is also lower than that of Examples 1, 2, 4, and 5. This indicates that hydrogen-containing silicone oil is crucial to the thermal stability of the thermally conductive interface layer and also affects its electrical conductivity.

[0092] The phase transition of the thermally conductive interface layer in Examples 1-5 is determined by the α-olefin-modified siloxane, specifically by the R12 group of the α-olefin-modified siloxane. Example 2 uses a different α-olefin-modified siloxane than Examples 1, 3, 4, and 5, specifically in the R12 group. Changing the number of carbon atoms in the R12 group alters the phase transition temperature of the thermally conductive interface layer. The phase transition temperature affects heat dissipation from the chip. The phase transition temperature in Example 2 is 40-42°C, higher than the 30-35°C in other examples. Correspondingly, the highest chip temperature in Example 2 is 68°C, higher than the 59-63°C in other examples.

[0093] During the thermal conductivity test of Comparative Example 1, the chip temperature gradually increased from 63°C to 73°C after 500 hours. The highest chip temperatures measured in the thermal conductivity experiments of Comparative Examples 1 to 5 all exceeded the preferred chip operating temperature range. The highest chip temperatures corresponding to Examples 1-5 were all lower than those of the Comparative Examples, and the highest chip temperatures of Examples 1, 3, 4, and 5 were within the preferred chip operating temperature range, indicating that the thermally conductive interface layer of the present invention has good thermal conductivity.

[0094] The phase change material of the present invention forms a more stable electrical-thermal conduction path (electronic thermal conduction path and phonon thermal conduction path) during long-term use. It is not easily degraded by aging overflow during long-term use, and therefore has better long-term thermal conductivity.

[0095] The breakdown voltages tested in Examples 1-5 were 5-7KV / mm, indicating that the thermally conductive interface layer of the present invention is a weakly insulating medium that can be adapted to chip heat dissipation and will not cause short circuit faults in the chip circuit during use.

[0096] While some embodiments of the present invention have been described in this application, those skilled in the art will understand that these embodiments are merely illustrative. Numerous variations, alternatives, and improvements will arise in those skilled in the art under the teachings of this invention without departing from its scope. The appended claims are intended to define the scope of the invention and thereby cover methods and structures within the scope of the claims themselves and their equivalents.

Claims

1. A thermally conductive interface layer containing nano-silver material, characterized in that, include: A thermally conductive material configured to conduct heat between a heat sink and a heat-generating element, the thermally conductive material comprising diamond micropowder and silver nanoparticles; as well as A phase change material is configured to undergo a reversible phase change to enter a viscoelastic state within the operating temperature range of a heating element, wherein the phase change material in the viscoelastic state promotes an increase in the thermal conductivity of a thermally conductive material, such that the phase change material is maintained within a temperature range consisting of a lower limit temperature and an upper limit temperature; the phase change material and the thermally conductive material are mixed together.

2. The thermally conductive interface layer containing nano-silver material according to claim 1, characterized in that, The lower limit temperature is between 15°C and 25°C, and the upper limit temperature is between 50°C and 70°C.

3. The thermally conductive interface layer containing nano-silver material according to claim 1, characterized in that, The phase change material is a silicon-based binder, formed by an addition reaction of hydrogen-containing silicone oil and α-olefin-modified siloxane: Hydrogen-containing silicone oil with the structure shown in Formula I: (Formula I), where 10≤a≤100, 2≤b≤50, 2≤c≤30, R1, R2, R3, R4, R7 are methyl, ethyl or C4~C8 straight-chain or branched alkyl, R6 is methyl, and R5 is C6~12 straight-chain or branched alkyl. α-olefin modified siloxanes with the structure shown in Formula II: (Formula II), R9, R10, R11, R13, and R14 are methyl, ethyl, or C6-C12 straight-chain or branched alkyl groups, R8 and R15 are alkenyl groups, R14 is methyl or C18-C30 straight-chain or branched alkyl groups, and 20 ≤ d ≤ 30.

4. The thermally conductive interface layer containing nano-silver material according to claim 3, characterized in that, R1, R2, R3, R4, R6, and R7 are methyl groups, and R5 is a C8 straight-chain or branched alkyl group; and / or R9, R10, R11, R13, and R14 are methyl, R8 is vinyl, R15 is vinyl, and R12 is a straight-chain or branched alkyl group of C24-C26 or C31-C39; and / or The molar ratio of hydrogen atoms in the Si-H of hydrogen-containing silicone oil to carbon-carbon double bonds in α-olefin-modified siloxanes is 0.5 to 1.

2.

5. The thermally conductive interface layer containing nano-silver material according to claim 1, characterized in that, The mass percentage of thermally conductive material in the thermal interface layer is greater than or equal to 90%; and / or The mass percentage of phase change material in the thermally conductive interface layer is 5%-8%.

6. The thermally conductive interface layer containing nano-silver material according to claim 1, characterized in that, The mass percentage of silver nanoparticles in the thermally conductive interface layer is 0.2%-3%. The nano-silver particles have a particle size of 1 nm-100 nm and are dispersed in the phase change material to form additional thermal conductivity pathways.

7. The thermally conductive interface layer containing nano-silver material according to claim 1, characterized in that, The nano-silver particles have a particle size of 5 nm-50 nm.

8. The thermally conductive interface layer containing nano-silver material according to claim 1, characterized in that, The thermally conductive material also includes one or more of the following: alumina, boron nitride, silicon carbide, zinc oxide, and aluminum powder.

9. The thermally conductive interface layer containing silver nanomaterial according to claim 8, characterized in that, The thermally conductive material includes diamond micron powder, zinc oxide, aluminum powder, and nano-silver particles.

10. The thermally conductive interface layer containing nano-silver material according to claim 1, characterized in that, The phase change material can chemically react with the metal surface of the cold plate and bond to the metal surface when heated to a certain temperature.